The Effect of Auditor Competence and Independence on Audit Quality at AYZ Company - Ambarwati, Rina; Rosidawaty, Rosidawaty; Gumilang, Andika Mugi; Sugiyono, Sugiyono; Dadang, Dadang; Aminudin, Dindin; Zuhro, Siti Fatimatul; Ramadhan, Muhammad Dhitya (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to see how auditor competence and independence affect audit quality. The background to this research is the importance of audit quality for stakeholders and the role of auditor competence and independence in improving audit quality. Data was collected through auditor reviews from various Public Accounting Firms (KAP). The research results show that the auditor's expertise and independence contribute significantly and positively to audit quality. In addition, the relationship between expertise and independence was also found to strengthen audit quality. This research shows that improving auditor education, training and experience and maintaining auditor independence are critical to producing high-quality audits.